PENGARUH SIZE, PROFITABILITAS, LOAN TO DEPOSIT RATIO, DAN KECUKUPAN MODAL TERHADAP OPINI AUDIT GOING CONCERN - Surya Handhayani, Ni Wayan; Budiartha, I Ketut (E-Jurnal Akuntansi, 2015)
Survival (going concern) an attempt is always associated with job performance has been achieved by the management company that is presented in the form of financial statements. This research aims to reexamine the effect of firm size, profitability, loan to deposit ratio, and capital adequacy of the going-concern audit opinion on the banking industry listed in Indonesia Stock Exchange. This research used 21 banking companies listed on the Stock Exchange from 2009 to 2012. Samples were obtained by purposive sampling. Data were analyzed using logistic regression analysis to determine whether or not the effect of firm size, profitability, loan to deposit ratio, and capital adequacy of the going concern audit opinion. The results of hypothesis testing, indicate that company size, profitability and credit growth has a negative relationship and there is no effect on the going concern audit opinion. The results of this research also showed that the capital adequacy does not affect the going concern audit opinion
Keywords: size, return on assets, loan to deposit ratio, capital adequacy ratio.